Role of microRNAs in Atrial Fibrillation: Establishment of Technological Pipeline - Apurva Shrivastava (2019)
arious important biological processes are governed by microRNAs (miRNAs) which are involved in fine-tuning of gene expression. Any discrepancies in the levels of certain miRNAs during a diseased state, such as arrythmogenesis, affects the pathways associated to cardiomyocyte metabolism and cardiac electrical and structural remodelling. Atrial fibrillation (AF) is a common arrhythmia affecting 1-2% of the population with evident risk of stroke and heart failure. It is necessary to characterize the disease at the molecular level since the involved pathways are not completely understood. In order to study and confirm the role of miRNAs in disease models such as AF, cell culture experimental approaches are commonly used. These experiments need to be established for each cell type and miRNA of interest. Within the symAtrial consortium, several miRNAs had been identified in association to AF, however, their function and mechanism in the pathology of AF is unknown and needs to be further investigated. The goal of this thesis was to establish a technological platform to aid in better characterization of the role of miRNAs in relation to AF. The thesis was divided into two aims: The first aim was to establish a technological pipeline with cell culture experiments to facilitate miRNA characterization. Two cell lines were used, one was the cell line of interest for AF–mouse atrial cardiomyocytes HL-1 cells, which are relatively difficult to culture and experiment with and the second cell line was HEK293, which is an easy-to-handle cell line. First the experimental conditions were established in HEK293 cells and were subsequently applied onto the HL-1 cell line. The transfection experiments included knockdown of a miRNA and measurement of its effect on cell viability and target mRNA levels. All experimental approaches were successfully established in HEK293 cells; however, for the HL-1 cells the similar experimental approaches failed. Consequently, the conditions had to be adapted for the HL-1 cells and a successful transfection was achieved. The second aim was to validate a set of miRNAs – miR-21, miR-100 and miR-483-5p, in samples of AF individuals. A housekeeper–miR-16 was used. However, the results of this thesis revealed that under the diseased condition of AF, miR-16 was deregulated. In conclusion, the technological pipeline using a cell culture platform was successfully established for HEK293 cells. For HL-1 cells, further experiments are required to establish the pipeline. In addition, a miRNA housekeeper stable under the diseased condition of AF is required, which could help identify dysregulated miRNAs in AF individuals. A candidate miRNA could be functionally characterised using the established cell culture platform.